2001
DOI: 10.1093/jac/47.5.617
|View full text |Cite
|
Sign up to set email alerts
|

In vivo efficacy of continuous infusion versus intermittent dosing of ceftazidime alone or in combination with amikacin relative to human kinetic profiles in a Pseudomonas aeruginosa rabbit endocarditis model

Abstract: Ceftazidime and amikacin were administered in a Pseudomonas aeruginosa rabbit endocarditis model using computer-controlled intravenous (iv) infusion pumps to simulate human serum concentrations for the following regimens: continuous (constant rate) infusion of 4, 6 or 8 g of ceftazidime over 24 h or intermittent dosing of 2 g every 8 h either alone or in combination with amikacin (15 mg/kg once daily). The in vivo activities of these regimens were tested on four Pseudomonas aeruginosa strains. Animals were kil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0
2

Year Published

2002
2002
2023
2023

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 23 publications
0
36
0
2
Order By: Relevance
“…The animals were then divided into six study groups, as follows: group A (n ϭ 10), control animals that received 30 ml of normal saline intravenously; group B (n ϭ 8), animals that received the clarithromycin regimen concomitantly with the inoculation of P. aeruginosa; group C (n ϭ 7), animals that received clarithromycin, as for animals in group B, and a second dose of clarithromycin exactly 2 h after bacterial challenge; group D (n ϭ 10), animals that received amikacin (Bristol) 30 min after bacterial challenge at a single intravenous bolus dose of 15 mg/kg, as proposed by others (19); group E (n ϭ 10); animals that received the clarithromycin regimen concomitantly with the inoculation of P. aeruginosa and amikacin 30 min after bacterial challenge; and group F (n ϭ 10), animals that received clarithromycin and amikacin, as for the animals in group E, and a second dose of clarithromycin exactly 2 h after bacterial challenge.…”
Section: Animalsmentioning
confidence: 99%
“…The animals were then divided into six study groups, as follows: group A (n ϭ 10), control animals that received 30 ml of normal saline intravenously; group B (n ϭ 8), animals that received the clarithromycin regimen concomitantly with the inoculation of P. aeruginosa; group C (n ϭ 7), animals that received clarithromycin, as for animals in group B, and a second dose of clarithromycin exactly 2 h after bacterial challenge; group D (n ϭ 10), animals that received amikacin (Bristol) 30 min after bacterial challenge at a single intravenous bolus dose of 15 mg/kg, as proposed by others (19); group E (n ϭ 10); animals that received the clarithromycin regimen concomitantly with the inoculation of P. aeruginosa and amikacin 30 min after bacterial challenge; and group F (n ϭ 10), animals that received clarithromycin and amikacin, as for the animals in group E, and a second dose of clarithromycin exactly 2 h after bacterial challenge.…”
Section: Animalsmentioning
confidence: 99%
“…15 times the MIC). It has been shown that against severe infections due to P. aeruginosa, for penicillins and cephalosporins not only the time that the antibiotic concentration remains above the MIC (T > MIC) but also the antibiotic concentration/MIC ratio are important criteria for improving survival [12]. In our work, only a high dosage (6 g/day) of CFZ was able to achieve bactericidal activity, and the best regimen was by CI.…”
Section: Discussionmentioning
confidence: 68%
“…In particular, continuous infusion of ␤-lactams has been studied. In vivo and in vitro studies have shown that, for the same daily dose, continuous infusion of ceftazidime improves the T Ͼ MIC compared to that obtained by intermittent dosing (9,17,22). The maximal activity of continuous infusion was obtained at a steady-state concentration in serum equal to a multiple of the MIC.…”
Section: Resultsmentioning
confidence: 98%